2018
DOI: 10.1002/imhj.21739
|View full text |Cite
|
Sign up to set email alerts
|

Does Fathers' Prenatal Mental Health Bear a Relationship to Parenting Stress at 6 Months?

Abstract: This study aimed to explore fathers' mental health and retrospectively reported adverse childhood experiences during pregnancy, as well as various pathways predicting self-reported stress at 6 months' postpartum as assessed by the Parenting Stress Index (PSI; R.R. Abidin, ). A total of 835 fathers contributed data to the study. Data collection comprised five time points during pregnancy and one at 6 months' postpartum. The main analyses were performed using linear regression and path analyses. First, linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…For example, Opacka-Juffry and Mohiyeddini (2012) found that ACEs are negatively related to oxytocin system functioning in adult men, suggesting increased susceptibility to stress. Moreover, it has been shown that ACEs among fathers bear a relation with depressive and anxious feelings during pregnancy ( Skjothaug et al, 2015 ), as well as with parenting stress at 6 months ( Skjothaug et al, 2018 ). Future studies should investigate whether fathers’ attachment style may be a mediating mechanism in the pathway between ACEs and later paternal stress, as was shown among mothers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Opacka-Juffry and Mohiyeddini (2012) found that ACEs are negatively related to oxytocin system functioning in adult men, suggesting increased susceptibility to stress. Moreover, it has been shown that ACEs among fathers bear a relation with depressive and anxious feelings during pregnancy ( Skjothaug et al, 2015 ), as well as with parenting stress at 6 months ( Skjothaug et al, 2018 ). Future studies should investigate whether fathers’ attachment style may be a mediating mechanism in the pathway between ACEs and later paternal stress, as was shown among mothers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fathers who reported several such experiences had more depressive symptoms and anxiety before birth of the child than those with lower scores. We also found that paternal symptoms of anxiety and depression during pregnancy as well as their own adverse childhood experiences predicted stress and a negative perception of the infants’ behaviour 55. In a similar vein, we investigated the multiple determinants of mothers’ parenting stress and found that partner attachment style assessed prenatally was a salient predictor of such stress 12 months after birth 18.…”
Section: Patient and Public Involvement Statementmentioning
confidence: 81%
“…The most important findings generated by the cohort so far can be summarised in three main domains. The first domain concerns parental mental health functioning in the perinatal period and factors related to parental anxiety, depression and stress in mothers and fathers 18 22 54 55. The second domain is directed towards child functioning and early detection of infants and toddlers at risk,23 51 52 56 while the third domain concerns maternal nutrition during pregnancy and its possible relation to early child development 32 57 58…”
Section: Patient and Public Involvement Statementmentioning
confidence: 99%
See 2 more Smart Citations